Relativization of Tor for HH of crossed products (Selecciones Matemáticas, 2022)
In this article, from the relativization of the functor Tor some properties of Hochschild homologies of crossed  products of Hopf are determined. The Hochschild homology functor of a product crossed satisfies the properties of a left satellite relative to an associated projective class of epimorphisms of an additive functor.
Keywords: Derived functors; natural equivalence of bifunctors; relative projective resolution; horseshoe lemma; Hochschild homologies